1984
DOI: 10.1128/jb.159.1.159-166.1984
|View full text |Cite
|
Sign up to set email alerts
|

Construction in vitro of a cloned nar operon from Escherichia coli

Abstract: To clone the nar operon of Escherichia coli without an effective selection procedure for the nar+ phenotype, a strategy utilizing nar::TnS mutants was employed. Partial segments of the nar operon containing TnS insertions were cloned into plasmid pBR322 by using the transposon resistance character for selection. A hybrid plasmid was constructed in vitro from two of these plasmids and isolated by a procedure that involved screening a population of transformed nar(Ts) mutant TS9A for expression of thermal stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Therefore, the NarK protein thus characterized as a strongly hydrophobic 140 transmembrane protein appears to be qualified enough to' form a channel-like structure. We assumed that the gene product is a nitrate transporter on the basis of: (i) the presence of a nitrate transporter has been demonstrated [ 1,7]; (ii) except for the narK gene, no coding capacity for the transport protein is apparently sustained in either the narCHJ1 operon or the downstream [9,10] and upstream regions [13,16]; (iii) the narK gene product is neither involved directly in the electron-transfer system [12] nor qualified as a regulatory protein [14-161; and (iv) the narK gene product shows remarkable characteristics as a typical transmembrane protein, as mentioned above.…”
Section: Analysis Of the Coding Nucleotide Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the NarK protein thus characterized as a strongly hydrophobic 140 transmembrane protein appears to be qualified enough to' form a channel-like structure. We assumed that the gene product is a nitrate transporter on the basis of: (i) the presence of a nitrate transporter has been demonstrated [ 1,7]; (ii) except for the narK gene, no coding capacity for the transport protein is apparently sustained in either the narCHJ1 operon or the downstream [9,10] and upstream regions [13,16]; (iii) the narK gene product is neither involved directly in the electron-transfer system [12] nor qualified as a regulatory protein [14-161; and (iv) the narK gene product shows remarkable characteristics as a typical transmembrane protein, as mentioned above.…”
Section: Analysis Of the Coding Nucleotide Sequencementioning
confidence: 99%
“…The mutants exhibit a normal level of nitrate reductase activity and regulate the expression of the nar operon [12]. However, Rondeau et al [9] reported that the narK mutant did not accuinulate nitrite in the overlay assay, assuming that either the nitrate reductase produced by this mutant is not functional or the ability for the cells to remove nitrite is derepressed. Based upon our observations, however, their result is consistently interpreted as a lack of normal transport of nitrate.…”
Section: Nitrate Transport Activitymentioning
confidence: 99%
“…It has been characterized both as a component of the active enzyme and as an isolated species [41]. It is encoded by the narl (previously chlI) gene which is part of the nitrate reductase nar operon [43]. The se-quence is not yet known, although the nar operon has been cloned [43].…”
Section: Cytochrome B5n~6 Is Labile and Easily Lost Inmentioning
confidence: 99%
“…It is encoded by the narl (previously chlI) gene which is part of the nitrate reductase nar operon [43]. The se-quence is not yet known, although the nar operon has been cloned [43]. Of particular interest is the role of this cytochrome in the assembly of the enzyme in the cytoplasmic membrane, as revealed by the examination of mutants which lack this subunit or cannot synthesize heme (hemA mutants) [41].…”
Section: Cytochrome B5n~6 Is Labile and Easily Lost Inmentioning
confidence: 99%
“…The genes which encode the three subunits of nitrate reductase are components of an operon, designated nar, which is transcribed in the order narG (ot subunit), narH (3 subunit), and narn (y subunit) (2,6,8,25). We have recently constructed in vitro a hybrid plasmid containing an intact nar operon which, in transformed strains, overproduces the three subunits of nitrate reductase under the control of the same factors which regulate the expression of the chromosomal operon (19).…”
mentioning
confidence: 99%